Identification of genes affecting milk fat and fatty acid composition in Vrindavani crossbred cattle using 50 K SNP-Chip - Singh, Akansha; Kumar, Amit; Gondro, Cedric; da Silva Romero, Andrea Renata [UNESP]; Karthikeyan, A.; Mehrotra, Arnav; Pandey, A. K.; Dutt, Triveni; Mishra, B. P. (Springer Nature, 2021)
The aim of this study was to identify candidate genes associated with milk fat per cent and fatty acid (FA) composition in Vrindavani cattle using the Illumina 50 K single-nucleotide polymorphism (SNP) array. After quality control, a total of 41,427 informative and high-quality SNPs were used for a genome-wide association study (GWAS) for milk fat percentage and 16 different types of fatty acids. Lactation stage, parity, test day milk yield, and proportion of exotic inheritance were included as fixed effects in the GWAS model. A total of 67 genome-wide significant (P < 1.20 × 10−06) SNPs and 176 suggestive significant (P < 2.41 × 10−05) SNPs were identified. Out of these, 15 SNPs were associated with more than one trait. The strongest associations were found on BTA14 for milk fat percentage and on BTA2 and BTA16 for polyunsaturated fatty acids. Several significant SNPs were identified close to or within the genes ELOVL6, FABP4, PMP2, PLIN1, MFGE8, GHRL2, and LDLRAD3 which are known to be associated with fat percentage and FA composition in dairy cattle breeds. This study is a step forward to better characterize the molecular mechanisms of phenotypic variation in milk fatty acids in a taurine–indicine composite cattle breed reared in tropical environments.
Keywords: Composite cattle; Genome-wide association studies; Milk fatty acid; Vrindavani cattle